A5. Bed rest reduces maternal total vascular resistance and enhances fetal growth. (12th August 2016) - Lo Presti, D.; Gagliardi, G.; Tiralongo, G. M.; Pisani, I.; Vasapollo, B.; Novelli, G. P.; Valensise, H.
Abstract: Objective : The objective of this study was to test the efficacy of bed rest in reducing total vascular resistance (TVR) in normotensive patients with TVR in the upper limits, evaluating the effect on fetal growth. Methods : Thirty women patients were enrolled between 27 and 29 weeks gestation. All the patients met the following criteria: normal blood pressure values before and during pregnancy, TVR between 1300 and 1400 dyne sec_1 cm_5, normal fetal Doppler parameters at enrollment, abdominal circumference between the 10th and 25th centile. The patients were randomly assigned to bed rest (15 patients, group A) or no treatment (15 patients, group B), and were then checked after 4 weeks to assess TVR and fetal growth. Results : TVR at enrollment, and abdominal circumference centile were similar in group A and B (1359 ± 26 versus 1344 ± 29 dyne, 16 ± 5 versus 17 ± 5 centile p = NS, respectively). After 4 weeks Group A showed a significant reduction of TVR associated to an increase in fetal growth versus group B (1165 ± 159 versus 1314 ± 190 dyne; 23 ± 6 versus 16 ± 4 centile; p < 0.05) and versus enrollment. Conclusions : Fetal growth is strictly linked to TVR. Bed rest appears to be effective in reducing TVR therefore enhancing fetal growth.